2018
DOI: 10.1111/cas.13744
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical characterization of B7‐H3 (CD276) expression and epigenetic regulation in diffuse brain glioma

Abstract: Gliomas are the most common malignant tumors of the brain. Immune checkpoints have been increasingly emphasized as targets for treating malignant tumors. B7‐H3 has been identified as an immune checkpoint that shows potential value for targeting therapies. We set out to characterize the expression pattern and biological function of B7‐H3 in brain gliomas using high‐throughput data obtained from the Chinese Glioma Genome Atlas (CGGA) and the Cancer Genome Atlas (TCGA) projects. B7‐H3 was upregulated more in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 27 publications
(38 reference statements)
8
75
2
Order By: Relevance
“…14,16,31 Existing evidence also indicates that higher B7-H3 expression is tightly correlated with poor prognosis in glioma patients. 32 In this study, we further confirmed the role of B7-H3 in glioma development and invasion, which is consistent with previous reports for other tumor types. 33 We found that B7-H3 induced the activation of JAK2/STAT3 signaling through the upregulation of phosphorylated Src and inhibition of the negative regulators SHP-1 and SOCS-3.…”
Section: Discussionsupporting
confidence: 93%
“…14,16,31 Existing evidence also indicates that higher B7-H3 expression is tightly correlated with poor prognosis in glioma patients. 32 In this study, we further confirmed the role of B7-H3 in glioma development and invasion, which is consistent with previous reports for other tumor types. 33 We found that B7-H3 induced the activation of JAK2/STAT3 signaling through the upregulation of phosphorylated Src and inhibition of the negative regulators SHP-1 and SOCS-3.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, an improved understanding of the possible causes of individual differences is needed to identify a subset of patients that may bene t from such treatments, thereby improving their current treatment. CD276 and HAVCR2 are key immune checkpoints in GBM, and its high expression is associated with poor prognosis in the patients [34,35,[39][40][41]. This observation is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…B7-H3 (CD276), a type I transmembrane protein belonging to the B7 family, is a glycoprotein consisting of 2 Ig-B7-H3 and 4 Ig-B7H3 isoforms in human. 3 B7-H3 is extensively known as a checkpoint molecular which is expressed on many tissues as well as immune cells. The enhanced expression of B7-H3 could down-regulate the type I interferon γ by T cells and reduce the cytotoxicity activity of NK cells, resulting in the immune suppression.…”
Section: Introductionmentioning
confidence: 99%